Difficulty and prospects of endovascular treatment for spontaneous intracranial artery dissection - Lei Shi; Lei Shi; Jinlu Yu (Frontiers in Neurology, 2025)
Intracranial artery dissections (IADs) are relatively uncommon. For ruptured IADs and unruptured IADs with acute large artery occlusion, the size increases significantly during follow-up, or there are signs of compression with mass occupation. Intervention can be suggested. Currently, endovascular treatment (EVT) is the choice for treating IADs. However, the understanding of EVT for IADs remains limited; therefore, a thorough review is necessary on the basis of a literature review and our experience. In this review, the following issues are discussed: the incidence and natural history of IADs, angiography of IADs, EVT indications for IADs, EVT techniques to treat IADs, the prognosis and complications of EVT for IADs, and EVT techniques for each IAD. After reviewing the literature and on the basis of our experience, the review revealed that when IADs need intervention, deconstructive or reconstructive EVTs can be chosen as an effective option on case-by-case basis to achieve a good prognosis.